THE INFLUENCE OF NGAYAH TRADITION AND EMOTIONAL INTELLIGENCE ON INTERPERSONAL RELATIONSHIPS IN BALINESE SOCIETY - Gita Nadia Maharani, Putu; Iksan, Mohamad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The COVID-19 pandemic disrupted Balinese social interactions, particularly the Ngayah tradition of mutual cooperation, while reducing emotional intelligence and interpersonal relationships. This study aimed to analyze the influence of Ngayah tradition and emotional intelligence on interpersonal relationships among Balinese people during and post-pandemic. Using an exploratory sequential mixed methods approach, the population comprised 2,000 active Ngayah participants, with 123 purposively sampled respondents. Instruments included Likert-scale questionnaires, semi-structured interviews, and non-participant observation, analyzed via SPSS multiple regression and NVivo thematic analysis. Results showed emotional intelligence (β=0.527, p<0.001) had stronger influence than Ngayah (β=0.231, p=0.026), explaining 47% of the variance (R²=0.470, F=32.129, p<0.001). Qualitative findings confirmed intensive Ngayah involvement enhances empathy through structured community activities. In conclusion, emotional intelligence primarily sustains relationships while Ngayah reinforces cultural solidarity, recommending emotion training integrated with local traditions for post-pandemic recovery.